Primary Graft Failure after Heart Transplantation. (12th June 2011) - Iyer, Arjun; Kumarasinghe, Gayathri; Hicks, Mark; Watson, Alasdair; Gao, Ling; Doyle, Aoife; Keogh, Anne; Kotlyar, Eugene; Hayward, Christopher; Dhital, Kumud; Granger, Emily; Jansz, Paul; et al.
Abstract : Primary graft failure (PGF) is a devastating complication that occurs in the immediate postoperative period following heart transplantation. It manifests as severe ventricular dysfunction of the donor graft and carries significant mortality and morbidity. In the last decade, advances in pharmacological treatment and mechanical circulatory support have improved the outlook for heart transplant recipients who develop this complication. Despite these advances in treatment, PGF is still the leading cause of death in the first 30 days after transplantation. In today's climate of significant organ shortages and growing waiting lists, transplant units worldwide have increasingly utilised "marginal donors" to try and bridge the gap between "supply and demand." One of the costs of this strategy has been an increased incidence of PGF. As the threat of PGF increases, the challenges of predicting and preventing its occurrence, as well as the identification of more effective treatment modalities, are vital areas of active research and development.